Urbanization and the verticality of rural–urban linkages in mountains - Haller, Andreas (2022)
Mountains are commonly considered a rural or even wild counterpart to cities. But, is this view still relevant in times of “planetary urbanization”? What is actually “wild,” “rural,” and “urban,” and how do these categories differ in structural and/or functional terms? Are there urban specificities in mountains? Drawing on the concepts of planetary urbanization and verticality, and introducing examples from the Global North and South, this chapter presents a central theme of urban montology, the sustainability-oriented, transdisciplinary study of urbanizing mountain environments: rural–urban linkages between altitudinal zones. Ecosystemic, infrastructural, demographic, economic, and sociocultural linkages in mountains present numerous peculiarities due to relief and altitude of the urbanizing environment. “Flows” of mountain ecosystem services, cable cars linking valleys and peaks, vertical spatial mobility of people, and the deliberate use of alpine environments and identities for branding mountain cities—to attract investors and visitors—are just a few examples that underline the increasing interconnectedness of the former counterparts of intrinsically “urban” cities and “rural” (or “wild”) mountains. This must be taken into account when studying and facilitating the transition of urbanizing mountain spaces into places worth living in for humans and nonhumans.